South Asia's ecosystems are a net carbon sink, but the region is a major net GHG source to the atmosphere - Jain, A. K.; Seshadri, S.; Anand, J.; Chandra, N.; Patra, P. K.; Canadell, J. G.; Chhabra, A.; Ciais, P.; Gilani, Hammad; Gumma, M. K.; Kondo, M.; Lokupitiya, E.; et al. (2025)
As part of the REgional Carbon Cycle Assessment and Processes‐2 (RECCAP‐2) project of the Global Carbon Project, here we estimate the GHG budgets (anthropogenic and natural sources and sinks) for the South Asia (SA) region as a whole and each country (Afghanistan, Bangladesh, Bhutan, India, Nepal, Pakistan, and Sri Lanka) for the decade of 2010–2019 (2010s). Countries in the region are experiencing a rapid rise in fossil fuel consumption and demand for agricultural land, leading to increased deforestation and higher greenhouse gas emissions. This study synthesizes top‐down (TD) and bottom‐up (BU) dynamic global vegetation model results, BU GHG inventories, ground‐based observation upscaling, and direct emissions for major GHGs. The fluxes for carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) analyzed include fossil fuel emissions, net biome productivity, land use change, inland waters, wetlands, and upland and submerged soils. Our analysis shows that the overall total GHG emissions contributed to a net increase of 34%– 43% during the 2010s compared to the 2000s, primarily driven by industrial activities. However, terrestrial ecosystems acted as a notable exception by serving as a CO2 sink in the 2010s, effectively sequestering atmospheric carbon. The sink was significantly smaller than overall carbon emissions. Overall, the 2010s GHG emissions based on BU and TD were 4,517 ± 639.8 and 4,532 ± 807.5 Tg CO2 eq, with CO2, CH4, and N2O emissions of 2165.2 ± 297.1, 1,404 ± 95.9, and 712 ± 466 Tg CO2 eq based on BU models 2,125 ± 515.1, 1,531 ± 205.2, and 876 ± 446.0 Tg CO2 eq based on TD models. Total emissions from SA in the 2010s accounted for approximately 8% of the global share. The terrestrial CO2 sinks estimated by the BU and TD models were 462.9 ± 195.5 and 210.0 ± 630.4 Tg CO2, respectively. Among the SA countries, India was the largest emitter contributing to 80% of the region's total GHG emissions, followed by Pakistan (10%) and Bangladesh (7%).